Pengaruh Faktor Diskriminasi, Keadilan dan Teknologi Informasi Terhadap Persepsi Wajib Pajak Mengenai Penggelapan Penggelapan Pajak di KPP Pratama Jember - Octavia Paramitha; Dwi Cahyono; Diyah Probowulan (Jurnal Akuntansi Profesi, 2020)
In this study intends to examine in order to obtain data on the influence of factors of discrimination, justice, technology and tax information on taxpayers' perceptions of tax evasion in the Jember Primary Tax Service Office. This type of research is quantitative and data sources are derived from primary data through questionnaires. The population in this study is individual taxpayers. The sampling technique in this study uses the Non-Probability Sampling method. So that the samples obtained were 100 respondents. The number of samples analyzed was 100 questionnaires and the data was analyzed using the Multiple Regression Test method. The results of this study are; discrimination and justice variables have a significant positive effect, while technology and information variables have a significant negative effect on taxpayers' perceptions of tax evasion in the Jember Pratama Tax Office.